FINANCIAL MANAGEMENT BEHAVIOR: FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE, & LOCUS OF CONTROL (STUDI PADA PELAKU UMKM DI DAERAH PESISIR MADURA) - Paramitha Candra Lukita Rahayu; M. Boy Singgih Gitayuda (Universitas Islam Balitar, 2023)
This study aimed to determine how financial attitude, financial knowledge, and locus of control affected the behavior of MSME actors in the coastal region of Madura, particularly with regard to financial management. Based on the results of the t-test, financial altitude shows a Sig value of 0.000, and t count shows a value of 6.631 meaning that the Sig value is less than the probability value of 0.05 (0.000 <0.05) and t count is greater than t table (6.631 > 2.003). The financial knowledge variable with the t-test value indicates a Sig value of 0.130 and t count indicates a value of 1.536 meaning that the Sig value is greater than the probability value of 0.05 (1.536 > 0.05) and t count is smaller than the t table (1.536 <2.003) and the locus variable of control the t-test shows al Sig value of 0.242 and t count shows a value of 1.182 meaning that the Sig value is greater than the probability value of 0.05 (0.242 > 0.05) and t count is smaller than t table (1.182 <2.003). The results of the F test showed that the calculated f value of 21.931 is greater than the f table of 2.766 and with a significance of 0.000. Because f count > f table and significance level < 0.05, the regression model can be said that financial attitude, financial knowledge, and locus of control simultaneously or simultaneously affect financial management behavior, while the test results for the coefficient of determination (R²) are obtained a value of 0.540 or 54% while 46% is influenced by other variables.